Development of the method for estimating the inertia radius relative to the vertical axis of the car - Podrigalo M. A.; Korobko А. I.; Dubinin E. A.; Tarasov Yu. V.; Baytzur M. V. (Журнал інженерних наук)
The method of estimating the inertia radius relative to the vertical axis of the car is proposed. This allows a third to reduce the relative error of its definition. A refined formula for calculating the radius of inertia design with respect to the vertical axis of the car is proposed. The use of the proposed formula reduces the error of determining the radius of inertia from 21–27 % to 5 %, and the error of determining the inertia moment for the car from 46– 61 % to 10 %. A method for assessing the adequacy of the results of theoretical and experimental studies is proposed. The use of the method has shown that the refined formula for calculating the radius of inertia relative to the vertical axis of the car makes it possible to reduce the probability of mismatching the results up to three times.